Oil Relations between China and Russia in Regional Science-Electrochemical Behavior of Organic Sulfur Compounds - Chen Jinling (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 4, 2023)
The main purpose of this paper is in the regional science demonstration fuel electrochemical hydrogenation desulfurization method. To begin, many sulphur compounds in fuels are summarised as thiophene, which is a typical material representative. Then, examine and evaluate the thiophene electrochemical hydrogenation desulfurization reaction mechanism. Moreover, typical of this oil in the thiophene sulfur compounds the reaction mechanism, by analogy, that the electrochemical hydrogenation of oil desulfurization method is feasible. Finally, apply this method to oil relations between China and Russia in regional science.